Make - Moyerman, Stephanie; Safari, an O'Reilly Media Company (San Francisco: 2016, 2016)
The Intel Edison is a crowning achievement of Intel's adaptation of its technology into maker-friendly products. They've packed the dual-core power of the Atom CPU, combined it with a sideboard microcontroller brain, and added in Wi-Fi, Bluetooth Low Energy, and a generous amount of RAM (1GB) and flash storage (4GB). This book, written by Stephanie Moyerman, a research scientist with Intel's Smart Device Innovation Team, teaches you everything you need to know to get started making things with Edison, the compact and powerful Internet of Things platform.
Electronic reproduction.
Mode of access: World Wide Web.
Made available through: Safari, an O'Reilly Media Company.
Keywords: Microcomputers; Electronic books